Proposed use of Wood Ash Water as a Remedy to Reducing Respirable Dust Exposure in a Copper Mine - Sifanu, Mwaba; Taylor, Thomas K.; Kalebaila, Kennedy K.; Hayumbu, Patrick; Nabiwa, Lubinda; Linde, Stephanus J. L.; Mweshi, Margaret M. (Disease and Health: Research Developments Vol. 8, 2025)
Exposure to respirable dust and respirable crystalline silica is frequently associated with work in the copper mining sector. This can result in silicosis, a chronic and irreversible occupational lung disease. This study aimed to establish the relationship between knowledge, attitudes, work behavioral practices and compliance with safety standards and workers’ exposure to respirable dust. A cross-sectional descriptive survey was conducted on 528 mine workers. The Statistical Package for Social Sciences (SPSS) was used for the descriptives. Structural equation modeling (SEM) with latent variables and partial least squares (LVPLS) analysis were employed to determine the relationship among these variables. The results indicated that of the four hypotheses, two were supported, and two were rejected, showing that there is a significant relationship between exposure to respirable dust and work behavioral practices, as well as compliance with safety standards. Knowledge and attitudes toward respirable dust exposure did not significantly influence exposure. The current study aimed at empirically establishing the relationship between knowledge, attitudes, work behavioral practices and compliance with safety standards for respirable dust exposure at mining sites. The findings of this study revealed that there was no direct significant relationship between knowledge of the risks and dangers of respirable dust, the attitudes of workers toward respirable dust and exposure to respirable dust. According to the results from the survey, positive work behavioral practices as well as compliance with safety standards were significantly associated with exposure to respirable dust. It is therefore recommended that wood ash water be used as a remedy to reducing respirable dust exposure in a copper mine. Mining operations should concentrate on improving miners’ work methods and ensure compliance with safety standards. Restoring lung functionality by undergoing lung re-expansion physiotherapy and promoting an improved quality of life, could also uphold health. The limitation of this study is that it measured knowledge, attitudes, work behavioral practices and compliance from miners at one mining site, which makes it difficult to generalize results to other mining sites.